Taxonomic notes on the genus Hedyotis sensu lato (Rubiaceae) in China - Wang, Rui-Jiang (Phytotaxa, 2019)
The genus Hedyotis sensu lato was splitted into several genera on basis of morphological and molecular evidences. Under this generic delimitation, seven new taxonomic treatments, including six new synonyms and one new combination, are proposed for the Flora of China. The name Hedyotis tenelliflora that misapplied to Scleromitrion angustifolium is also corrected with morphological comparison.